Growth, forage yield and seed yield components responses of some bitter vetch (Vicia ervilia) varieties to different seeding rate in Sulamani Region - Rafaat , Jwan Gharib; Mahamood , Ako Hussein; Ghareeb, Shaee Adeeb (Journal of Kerbala for Agricultural Sciences, 2024)
A field trial investigated the impact of varying seeding rates; 60 kg ha-1, 80 , 100 , and 120 Kg ha-1 on the growth, forage yield, and yield components of three bitter vetch (Vicia ervilia) varieties (Perper from Serbia, Larnaca, and Tarsan-2). The experiments were conducted during the winter season of 2022-2023 in the Sulaimani governorate at Qlyasan locations. A factorial design was employed, and the experiment was arranged in a Randomized Complete Block Design (RCBD) with three replications. Mean comparisons were performed using the Duncan test. Results indicate that a seeding rate of 60 Kg ha-1 resulted in optimal plant height (96.644 cm). The parameters Days to 50% flowering and days to maturity reached maximum values of 121.831 and 157.614, respectively, with an 80 Kg ha-1seeding rate. Dry leaf weight peaked at 1.129 g with the same seeding rate. Tarsan-2 exhibited the highest dry leaf weight (1.045 g), while variety number 2 showed the highest dry stem weight (3.746 g). Additionally, a seeding rate of 60 kg/ha combined with variety number 1 yielded the tallest plants (103.800 cm).Tarsan-2, in conjunction with a seeding rate of 120 , demonstrated the longest durations for Days to 50% flowering (127.300 days) and days to maturity (164.240 days), as well as the highest dry leaf weight (4.153 g). The maximum fresh yield was recorded at 24.699 ton/ha and 24.456 ton/ha with seeding rates of 100 Kg ha-1 and 120 Kg ha-1, respectively. Variety number 2, seeded at 60 Kg ha-1, exhibited the highest number of pods per plant (22.110). Conversely, variety number 1, when seeded at a rate of 100 Kg ha-1, yielded the highest 100-seed weight (22.073 g), seed yield (5.801 Mg ha-1), and harvest index (0.326).